Physiological and behavioral responses of phytoplankton communities to nutrient availability in a disturbed Mediterranean coastal lagoon. (5th April 2019) - Leruste, A.; Pasqualini, V.; Garrido, M.; Malet, N.; De Wit, R.; Bec, B.
Abstract: Short-term bioassays were conducted in Biguglia lagoon (Corsica) to study the physiological and behavioral responses of phytoplankton to N- and P-availability. Natural communities were collected in two stations representative of the two sub-basins, at three periods with contrasting environmental characteristics to address the impact of seasonal variability. These samples were separately enriched with a full N and P enrichment, and with enrichments minus N or minus P. Phytoplankton size structuration, diversity, and growth of the total phytoplankton, the micro-, nano- and ultraphytoplankton were evaluated using spectrofluorimetry, and optical microscopy. Results showed that the communities were fueled by NO3 − in the wet periods (autumn and spring) and NH4 + in summer. The phytoplankton communities displayed highest cell size in autumn, with high abundances of nanoflagellates, and smallest cell size in summer with a large dominance of phycocyanin-rich picocyanobacteria. Blooms of dinoflagellates also occurred during the wet periods, coinciding with high N:P ratios. The full enrichment has not stimulated phytoplankton growth in autumn, suggesting the importance of other controlling factors such as light, a possible NH4 + inhibition or the use of mixotrophic abilities. In spring, communities have displayed single P-limitation in the northern basin and different N and P co-limitations in the southern basin. In summer, the full enrichment consistently stimulated the growth of all cell sizes. The communities showed high N and P co-limitations, which is consistent with growing observations in aquatic ecosystems, and reflects the different functional responses of phytoplankton communities to the nutrient availability. Graphical abstract: Chlosrophyll a (Chl a ) concentration, DIN:DIP ratio, main taxa/morphotypes, response to the full nutrient enrichment, and N- and/or P-limitation during the three bioassay periods in the two stations representatives of the Northern and the Southern basins of Biguglia lagoon.Image 1 Highlights: Freshwater inputs from the watershed strongly influenced the phytoplankton of Biguglia lagoon. Nanoflagellates dominated phytoplankton communities in autumn and spring with high N:P ratios. Phycocyanin-rich picocyanobacteria bloomed in the sampling in September with low N:P ratios. Phytoplankton showed differential responses to nutrient enrichments and induced limitations. Phytoplankton was generally co-limited by N and P, with exceptions depending on seasons.